Bacterial reduction in river water using nanocellulose membrane from pineapple biomass with ferrous-ferric oxide reinforcement - D. Syukri; H. Suryanto; F. Kurniawan; P.D. Hari; R.M. Fiana; . Rini (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Constructing a nanocellulose membrane from biomass waste can lessen harmful environmental effects owing to its ability to absorb chemical and microbiological impurities. Therefore, nanocellulose membranes with magnetic properties were developed as a powerful apparatus for reducing microbials and dyes in water.METHODS: In this study, bacterial cellulose acetate-based nanocomposite membrane with ferrous-ferric oxide nanoparticle reinforcement was produced from pineapple peel biowaste extract through fermentation and esterification. High-pressure homogenization was used to produce nano properties of cellulose from pineapple. Meanwhile, the ultrasonic homogenizer was used to mix the produced nanocellulose with the ferrous-ferric oxide with various treatment (0.25, 0.50, 0.75, and 1.0 weight percent of cellulose acetate) to produce nanocomposite membrane. The membrane was then applied for the removal of bacteria and dyes. The samples were water from local rivers located near industries such as rubber, cement, and tofu industries. The effectiveness of the nanocomposite membrane at bacteria and dyes reduction was assessed.FINDINGS: Nano cellulose membrane effectively reduced gram-negative bacteria and anionic dyes in the water samples. The ferrous-ferric oxide reinforcement enhanced the effectiveness of the membrane on bacteria and dye reduction. The addition of ferrous-ferric oxide resulted in a greater amount of dye degradation, and the presence of ≥0.75 percent ferrous-ferric oxide indicated an optimum ability to kill bacteria.CONCLUSION: Ferrous-ferric oxide yielded good results in reducing the number of microbes and anionic dyes in the water samples tested. The results of this research can be used as basic data to advance the use of nanocellulose membranes as a biomaterial for controlling environmental impacts.